A Comparative Study between Helicobacter Pylori Antigen in Stool with Histopathology and Rapid Urease Test of Endoscopic Biopsy in PUD Patient (Community Based Medical Journal, 2021)
Purpose: To assess stool antigen test as an early effective diagnostic tool like other methods for the diagnosis of H. pylori infection in PUD patient.Patients and Methods: This cross-sectional study was carried in a clinical pathology department of a tertiary level hospital. We included all patients with peptic ulcer disease those who were diagnosed by upper GIT endoscopy. Demographic variables and value of laboratory test including Stool antigen test, rapid urease test was studied in this study.Result: A total of eighty-six patients were undergone for endoscopy after tested for Helicobactor pylori antigen in stool. Among 86 study subjects, Male was 56 (65%) and female was 30 (35%). The Mean (±SD) age was found 38.53(±10.40) years with range from 21 to above 60 years. Stool antigen test positive in 66 (66/86, 76.74%), negative in 20 (20/86, 23.3%). Rapid Urease Test positive in 76 (76/86, 88.4%), negative in 20 (20/86, 11.6%). Histopathology positive in 65 (65/86, 75.58%), negative in 21 (21/86, 24.42%). The result was statistically highly significant (P